UPAYA MENINGKATKAN EFEKTIVITAS HASIL PEBELAJARAN LARI GAWANG MELALUI PERMAINAN LARI KIJANG PADA SISWA KELAS IV SD NEGERI 01 KENDALDOYONG KECAMATAN PETARUKAN KABUPATEN PEMALANG TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the increase in learning hurdles deer run through the game in grade IV Elementary School District 01 Kendaldoyong Petarukan Pemalang Academic Year 2012/2013. This research was conducted with classroom action research. Object of this study is the fourth grade students of SD Negeri 01 Kendaldoyong second semester of the school year 2012/2013 amounted to 35 students. The instrument used to collect data in this study is the observation sheets, questionnaires and tests students' performance. The results showed an increase in learning hurdles deer run through the game 40% of the initial conditions, the first cycle of 82.85% and 94.28% in the second cycle, as well as the results of this study showed an increase in students' mastery of learning outcomes of the initial conditions for kesiklus II 54.28%. Conclusion This study shows that exercise effective deer fled to improve learning outcomes hurdles at the fourth grade students of SD Negeri 01 Kendaldoyong sub Petarukan Pemalang Academic Year 2012/2013.